Enhancing Social Responsibility and Sustainability in Real Estate Industry (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study delivers a full insight into the current state of research on socialresponsibility and sustainability in developing countries. It aims to point out the relevanceof social responsibility and sustainability issues, the need for their enhancement as the toppriority for business entities. Furthermore, it also highlights ways to enhance sustainabilityand social responsibility in real estate industry of developing countries. The growth of realestate industry brings risks of unsustainability to developing countries. Thus, it is a mustfor real estate businesses to enhance a sustainable model of development throughpromoting sustainable leadership and integrating corporate culture. As such, the study isthe first toemphasise the role of sustainable leadership in promoting sustainable model ofdevelopment in the real estate industry of developing countries